Efektivitas Pembelajaran Online pada Pelajaran Pendidikan Agama Islam di SMP Negeri Terusan Musi Rawas Utara - Dianto Busro (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The results of research and discussion, regarding the effectiveness of students’ online learning towards the learning interest of Islamic religious education at the Terusan Musi Rawas State Junior High School in North Sumatra, the researchers conclude as follows: 1. That the interest of students in online learning is quite large, this can be seen from the activeness of the students. in learning their attendance is quite active, and the assignments given are always collected, even though some are late, due to signal interference, but do not dampen their enthusiasm. 2. The effectiveness of online Islamic education learning at SMP Negeri Terusan Musi Rawas Utara, South Sumatra Based on the results of the research that the researcher conducted, that by learning PAI online, teachers can use technology to make learning effective and efficient, but don’t forget to take action that understands the condition of students because in reality students in online learning do not always have smooth signals. There are even some children who don’t have their own cellphones. But learning PAI for these students using the online method is quite effective. It can be seen that most students follow the learning process actively, only a small proportion are less active due to signal interference and problems with their cellphones.